X‐ray asterism and the structure of cracks from indentations in silicon. (1st February 2016) - Tanner, B. K.; Garagorri, J.; Gorostegui-Colinas, E.; Elizalde, M. R.; Allen, D.; McNally, P. J.; Wittge, J.; Ehlers, C.; Danilewsky, A. N.
Abstract : The origin of asterism in X‐ray diffraction images of cracks in silicon is shown to be associated with tilted material just prior to breakout. Cracks around indentations reflect the indenter tip geometry, not the specimen crystallography, and surface‐breaking Palmqvist cracks are found to be directly connected to the median sub‐surface cracks, the presence of extensive lateral cracks being a prerequisite for material breakout. Abstract : The asterism observed in white radiation X‐ray diffraction images (topographs) of extended cracks in silicon is investigated and found to be associated with material that is close to breakout and surrounded by extensive cracking. It is a measure of the mechanical damage occurring when the fracture planes do not follow the low‐index cleavage planes associated with the crystal structure. It is not related to a propensity for some cracked wafers to shatter during subsequent high‐temperature processing. There is no correlation between crack morphology and alignment of an indenter with respect to the orientation of a silicon wafer, the cracks being generated from the apices of the indenter and having threefold symmetry for Berkovich indents and fourfold symmetry for Vickers indents. X‐ray diffraction imaging (XRDI) of indents does not reveal this underlying symmetry and the images exhibit a very substantial degree of variation in their extent. This arises because the XRDI contrast is sensitive to the long‐range strain field around the indent and breakout reduces the extent of this long‐range strain field. Breakout is also detected in the loss of symmetry in the short‐range strain field imaged by scanning micro‐Raman spectroscopy. Weak fourfold symmetric features at the extremes of the images, and lying along ⟨110⟩ directions, are discussed in the context of slip generated below the room‐temperature indents. Scanning electron microscopy imaging of the region around an indent during focused ion beam milling has permitted the three‐dimensional reconstruction of the crack morphology. The surface‐breaking Palmqvist cracks are found to be directly connected to the median subsurface cracks, and the presence of extensive lateral cracks is a prerequisite for material breakout at indenter loads above 200 mN. The overall crack shape agrees with that predicted from simulation.